PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PINJAMAN MODAL USAHA BERBASIS FINTECH BAGI PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Mellisa Rahmaini Lubis (Indonesia Private Law Review, 2020)
Consumers loses have occurred in the practice of Fintech-based loans by non-bank financial institutions. The reports of losses arising from Fintech transactions has increased. This is because many Fintech organizers have not received permission from the OJK but are still able to conduct business activities in Indonesia. The problem in this study is: How is the supervision by the Financial Services Authority (OJK) of non-bank financial institutions providing fintech-based venture capital lenders for MSMEs? And how is the legal consequences of fintech-based business capital loan services for MSME entrepreneurs. The study used normative legal approach and the data analyzed by descriptive qualitative.The results of this study indicate that supervision by the OJK of non-bank financial institutions providing fintech-based venture capital lenders for SMEs as a form of legal protection to consumers. It is carried out in the form of preventive and repressive protection. Preventive protection is implemented by enacting OJK Regulation Number 77 / POJK.01 / 2016, OJK Circular Letter Number 18 / SEOJK.02 / 2017 and OJK Regulation Number 1 / POJK.07 / 2013 concerning Consumer Protection in the Financial Services Sector. Repressive protection is by applying sanctions against fintech organizers who commit violations in the form of written warnings and fines; restrictions on business activities; and revocation of permission. The legal consequences arising from fintech-based business capital loan services for SMEs to fintech providers are required to improve standards and meet consumer protection aspects. The legal consequence for MSMEs is the potential for fraud and misuse of consumer data by Fintech service providers.